Determination of Tropomyosin in Shrimp and Crab by Liquid Chromatography–Tandem Mass Spectrometry Based on Immunoaffinity Purification - Fan, Sufang; Ma, Junmei; Li, Chunsheng; Wang, Yanbo; Zeng, Wen; Li, Qiang; Zhou, Jinru; Wang, Liming; Wang, Yi; Zhang, Yan (Frontiers in Nutrition, 2022)
A UPLC-MS/MS method was developed for the detection of tropomyosin (TM) in shrimp and crab. After simple extraction, the samples were purified by immunoaffinity column and then digested by trypsin. The obtained sample was separated by Easy-nLC 1000-Q Exactive. The obtained spectrums were analyzed by Thermo Proteome Discoverer 1.4 software and then ANIQLVEK with high sensitivity was selected as the quantitative signature peptide. Isotope-labeled internal standard was used in the quantitative analysis. The method showed good linearity in the range of 5–5,000 μg/L with a limit of quantification (LOQ) of 0.1 mg/kg. The average recoveries were 77.22–95.66% with RSDs ≤ 9.97%, and the matrix effects were between 88.53 and 112.60%. This method could be used for rapid screening and quantitative analysis of TM in shrimp and crab. Thus, it could provide technical support for self-testing of TM by food manufacturers and promote further improvement of allergen labeling in China.